Analysis of Logistic Inventory Control for Disaster at the Office of Social Services in Pasangkayu Regency - Akkas, Nasrulhak; Budi Arnawa, I Made; Farid, Farid; Salmiati, Salmiati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
The process of providing logistics at the Pasangkayu Regency Social Service is by the Regulation of the Minister of Social Affairs of the Republic of Indonesia Number: 82 / HUK / 2005, concerning the Organization and Work Procedure of the Ministry of Social Affairs of the Republic of Indonesia, starting from a recording or identifying and assessing needs including logistics and equipment, from which assistance is received, what kind of help, how much and how to use it. The research objective was to identify and analyze the logistics supply control for disasters at the Pasangkayu Regency Social Service Office. The research method uses the Economical Order Quantity method in minimizing the cost of logistics supplies at the Pasangkayu Regency Social Service. The reporting system carried out by warehouse officers at the Pasangkayu Social Service provides information about logistical data/goods in the warehouse and is made periodically and continuously from releasing and distributing logistics/goods. In carrying out the Economic Order Quantity (EOQ) method, which aims to get the optimum number of orders, of course, it must be supported by an information system that can find out the amount of use of each logistics available at the Pasangkayu Regency Social Service Warehouse.